Dark current reduction in stacked-type CMOS-APS for charged particle imaging. - Takayanagi, I. (IEEE Transactions on electron devices)
A stacked CMOS-active pixel sensor (APS) with a newly devised pixel structure for charged particle detection has been developed. At low operation temperatures (<200 K), the dark current of the CMOS-APS is determined by the hot carrier effect. A twin well CMOS pixel with a p-MOS readout and n-MOS reset circuit achieves low leakage current as low as 5×10-8 V/s at the pixel electrode under liquid nitrogen temperature of 77 K. The total read noise floor of 0.1 mVrms at the pixel electrode was obtained by nondestructive readout correlated double sampling (CDS) with the CDS interval of 21 s.